Epidemiology of Infectious Pathogens in Horses with Acute Respiratory Disease, Abortion, and Neurological Signs: Insights Gained from the Veterinary Surveillance System for Horses in The Netherlands (SEIN) - Kees van Maanen; Linda van den Wollenberg; Tara de Haan; Thibault Frippiat (Veterinary Sciences, 2025)
Monitoring infectious diseases is essential for safeguarding equine health and ensuring the sustainability of the horse industry. In 2019, the Royal Veterinary Association of the Netherlands (KNMvD) and Royal GD (GD Animal Health) launched SEIN (Surveillance of Equine Infectious diseases in the Netherlands), a voluntary surveillance system for laboratory-confirmed outbreaks of equid alphaherpesvirus 1 (EHV-1), equid alphaherpesvirus 4 (EHV-4), equine influenza virus (EIV), and Streptococcus equi subsp. equi. This retrospective study analyzed 364 confirmed outbreaks reported through SEIN between June 2019 and April 2023. S. equi was the most commonly reported pathogen overall (64%). Among outbreaks involving respiratory disease, S. equi accounted for 74% of cases, followed by EHV-4 (16%), EIV (6%), and EHV-1 (4%). The geographical distribution of outbreaks covered 80 of the 90 postal code regions (89%), and approximately half of all participating practices generated at least 1 alert. Vaccination data revealed low coverage against EHV-1/4, EIV, and S. equi among both affected horses and premises. Clinical signs overlapped between pathogens, but some were more pathogen-specific, e.g., coughing in EIV, and abscessation in S. equi. The SEIN system provided spatiotemporal information on confirmed outbreaks. These results underscore the importance of quick diagnostics and structured surveillance systems in guiding prevention strategies.